2014
DOI: 10.1007/s11121-014-0529-4
|View full text |Cite
|
Sign up to set email alerts
|

A Theory-Based Intervention to Improve Breast Cancer Awareness and Screening in Jamaica

Abstract: Despite declines in breast cancer mortality rates in developed countries, mortality rates remain high in Jamaica due to low levels of screening and lack of early detection. We hypothesized that a theory-based health educational intervention would increase awareness of breast cancer and intention to screen among women in Western Jamaica. Two hundred and forty six women attending hospitals or clinics were enrolled in an educational intervention consisting of a pretest, breast cancer presentation, and posttest if… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 20 publications
4
7
0
Order By: Relevance
“…Moreover, the independent effect of the program was demonstrated through multivariate analysis, which provides further confirmation of its effectiveness. In agreement with these findings, a study in Jamaica reported statistically significant improvements in women's knowledge about breast cancer following an educational program (Anakwenze et al, 2014). Similar improvements were reported by Lee-Lin et al (2014) in a randomized clinical trial on the effects of a breast health intervention on the knowledge and beliefs among Chinese American immigrants.…”
Section: Discussionsupporting
confidence: 74%
“…Moreover, the independent effect of the program was demonstrated through multivariate analysis, which provides further confirmation of its effectiveness. In agreement with these findings, a study in Jamaica reported statistically significant improvements in women's knowledge about breast cancer following an educational program (Anakwenze et al, 2014). Similar improvements were reported by Lee-Lin et al (2014) in a randomized clinical trial on the effects of a breast health intervention on the knowledge and beliefs among Chinese American immigrants.…”
Section: Discussionsupporting
confidence: 74%
“…In the same line, a study by Ahmed et al (2017), Revealed that more than two-fifths of adolescent girls their practices about BSE improved post interventions, also agree with. A study carried out by Anakwenze et al (2015), contradicted with the results of the current study, These results were also consistent with Ramadan and Mohamed 2015, who revealed that there was a significant improvement in the level of women's practice of BSE after the program implementation.…”
Section: Discussionsupporting
confidence: 85%
“…A study conducted in Jamaica reported that 11.4% of women had undergone a mammography at least 5 years ago 45 .…”
Section: Resultsmentioning
confidence: 99%